Equilibrium constant for carbamate formation from monoethanolamine and its relationship with temperature - Aroua, Mohamed Kheireddine; Benamor, A.; Haji-Sulaiman, M.Z. (American Chemical Society, 1999)
The equilibrium constant for the formation of carbamate from monoethanolamine (MEA) was evaluated at various temperatures of 298, 308, 318, and 328 K and ionic strength up to 1.7 M. The equilibrium constant has been estimated by extrapolating the value of the calculated apparent equilibrium constant to zero ionic strength. A relationship on its variations with temperature is also proposed.